Los espacios del pregón - Lilián Illades (Nuevo mundo - Mundos Nuevos, 2008)
The West Indies were recipients of the Castilian political and legal organization, most particularly the municipal organization under the authority of a city council. During the sessions, the aldermen decided what information should be notified to the inhabitants, as well as the penalties in the event of non compliance with the rules and regulations. The severity of the penalty depended on the ethnic group of the offenders. The town crier, through his proclamations, transmitted to the population the general and urgent agreements related to the distribution and ownership of land, revenues of the municipality, ecclesiastical and civil festivities and celebrations, procurement of goods, street and town cleaning, public works, trades, as well as royal regulations. The crier was the mean of communication between the government and a society, based primarily upon the spoken word.